Mediastinal lymph node dissection versus mediastinal lymph node sampling for early stage non-small cell lung cancer: a systematic review and meta-analysis. - Xiongfeng Huang; Jianmin Wang; Qiao Chen; Jielin Jiang (PLoS ONE)
Objective This systematic review and meta-analysis aimed to evaluate the overall survival, local recurrence, distant metastasis, and complications of mediastinal lymph node dissection (MLND) versus mediastinal lymph node sampling (MLNS) in stage I-IIIA non-small cell lung cancer (NSCLC) patients. Methods A systematic search of published literature was conducted using the main databases (MEDLINE, PubMed, EMBASE, and Cochrane databases) to identify relevant randomized controlled trials that compared MLND vs. MLNS in NSCLC patients. Methodological quality of included randomized controlled trials was assessed according to the criteria from the Cochrane Handbook for Systematic Review of Interventions (Version 5.1.0). Meta-analysis was performed using The Cochrane Collaboration's Review Manager 5.3. The results of the meta-analysis were expressed as hazard ratio (HR) or risk ratio (RR), with their corresponding 95% confidence interval (CI). Results We included results reported from six randomized controlled trials, with a total of 1,791 patients included in the primary meta-analysis. Compared to MLNS in NSCLC patients, there was no statistically significant difference in MLND on overall survival (HR = 0.77, 95% CI 0.55 to 1.08; P = 0.13). In addition, the results indicated that local recurrence rate (RR = 0.93, 95% CI 0.68 to 1.28; P = 0.67), distant metastasis rate (RR = 0.88, 95% CI 0.74 to 1.04; P = 0.15), and total complications rate (RR = 1.10, 95% CI 0.67 to 1.79; P = 0.72) were similar, no significant difference found between the two groups. Conclusions Results for overall survival, local recurrence rate, and distant metastasis rate were similar between MLND and MLNS in early stage NSCLC patients. There was no evidence that MLND increased complications compared with MLNS. Whether or not MLND is superior to MLNS for stage II-IIIA remains to be determined.